2015
DOI: 10.1016/j.celrep.2015.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Structure Guided Design of Potent and Selective Ponatinib-Based Hybrid Inhibitors for RIPK1

Abstract: Summary RIPK1 and RIPK3, two closely related RIPK family members, have emerged as important regulators of pathologic cell death and inflammation. In the current work, we report that the Bcr-Abl inhibitor and anti-leukemia agent ponatinib is also a first-in-class dual inhibitor of RIPK1 and RIPK3. Ponatinib potently inhibited multiple paradigms of RIPK1- and RIPK3-dependent cell death and inflammatory TNFα gene transcription. We further describe design strategies that utilize the ponatinib scaffold to develop t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
136
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(140 citation statements)
references
References 39 publications
3
136
0
Order By: Relevance
“…In addition to benefiting basic science, a holistic understanding of the biology and mechanism of RIP kinase activation is important for potential therapeutic targeting of these molecules in inflammatory diseases. In this regard, RIPK1 and RIPK3 inhibitors have been developed [56, 95, 98101]. Developing inhibitors that can target additional inflammatory pathways beyond necroptosis may magnify therapeutic potential of RIP kinase-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to benefiting basic science, a holistic understanding of the biology and mechanism of RIP kinase activation is important for potential therapeutic targeting of these molecules in inflammatory diseases. In this regard, RIPK1 and RIPK3 inhibitors have been developed [56, 95, 98101]. Developing inhibitors that can target additional inflammatory pathways beyond necroptosis may magnify therapeutic potential of RIP kinase-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…This was explained by an increased flexibility of the activation loop of human kinase, which was necessary to accommodate the major conformational changes in the activation segment, the C-helix, and the glycine-rich loop upon compound binding. We have previously reported that the DLG motif of RIPK1 (as opposed to DFG present in the majority of the kinases) was also essential in providing flexibility to the allosteric pocket of RIPK1 [125]. These data reveal that the allosteric back pocket of RIPK1 possesses unusual flexibility, which allows development of small molecule inhibitors with unprecedented specificity.…”
Section: New Inhibitors Of Ripk1 and Ripk3mentioning
confidence: 93%
“…This includes synthesis of TNFα, and the generation of an auto-feedback loop promoting apoptotic cell death and expression of multiple cytokines and chemokines [74, 123, 124]. These responses required kinase activity of RIPK1 and RIPK3, acting in a kinase and MLKL-independent manner [74, 125]. SMAC mimetics were also shown to promote IL-1β processing by both NLRP3 and caspase-8 inflammasomes, which was abolished in Ripk3 -/- cells [89].…”
Section: Emerging Roles Of Ripk1 and Ripk3 In Cancermentioning
confidence: 99%
See 2 more Smart Citations